Manajemen Sumber Daya Manusia untuk Peningkatan Kemitraan Smallholder: Model untuk Keberlanjutan Perkebunan Kelapa Sawit - Widi Amalia; Marzuti Isra; Suhendri Suhendri; Purjianto Purjianto; Agung Rizky Syah Alam Harahap; Asri Ansya Ritonga; Bayu Saksena; Fatur Rahman Hasibuan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The development of the palm oil industry in Indonesia typically relies on collaboration with smallholder farmers, but this collaboration often faces various problems such as poor cultivation techniques, lack of technical guidance, unclear administrative matters, and limited access to certification and markets. This study aims to develop a specific human resource management model to support collaboration with smallholder farmers, thereby improving production yields, sustainability, and engagement in the palm oil supply chain. The method used is a desk study, namely by analyzing and reconstructing information from research results, industry reports, and palm oil certification and sustainability policies. Based on the analysis, a career structure and Human Resource Management functions are proposed, consisting of collaboration supervisors, field officers, capacity training officers, collaboration administration staff, and collaboration/certification managers. This model allows for technical and administrative assistance, training for farmers, collaboration coordination, and certification and compliance management. The implementation of this model is predicted to improve cultivation quality, improve smallholder access to certification and markets, and strengthen the stability and sustainability of the supply chain. Thus, the HR model for smallholders offers a strategic solution to the various challenges of working with smallholders and supports the development of a socially, economically, and environmentally sustainable palm oil agribusiness sector.